THE EMERALD ATLAS - Stephens, John, 1972- (The books of beginning ;, 2011)
In order to protect them, Kate, Michael, and Emma have passed from one orphanage to another in the ten years since their parents disappeared but now they learn that they have special powers, a prophesied quest to find a magical book, and a fearsome enemy.